Compilation of qualitative researches /BS Psychology IV-2 - Abodo, Danny;Castro, Freya; Dela Cerna, Corinne, et. al. 4 0 16; 5
NO ABSTRACT.
Open-Minded ka Ba sa Business?:Filipinos' Views of Network Marketing.----- NO ABSTRACT.;Can You Read my Mind? How Filipinos Stereotype Psychology Majors.-----NO ABSTRACT.;Panganay Ako Eh!: Power Trip Among First Born Filipino Children.-----NO ABSTRACT.;Aw,Aw, Away: Dogs and their Positive Effects to Pet Owners.-----NO ABSTRACT.
Undergraduate Thesis: (B.S. Psychology)- Pamantasan ng Lungsod ng Maynila, 2016.
Keywords: 2 -- 0; 6; 20; 20; 2